Integration of Rationality and Spirituality: A Comparative Study of Educational Thought Ibn Sina and Aristotle - Chaniago, Azharida; Saputri, Restu Arya (DAS Institute, 2025)
This study examines the comparative philosophical foundations of education in Islamic and Western traditions by analyzing the thoughts of Ibn Sina (Avicenna) and Aristotle. Both philosophers share a profound concern for human perfection and intellectual development, yet they differ fundamentally in their epistemological orientations and ultimate goals. Aristotle’s philosophy emphasizes rational empiricism and the actualization of human potential through moral and intellectual virtue, whereas Ibn Sina integrates rational inquiry with spiritual transcendence grounded in Islamic metaphysics and the concept of tawhid (unity of God). The comparative analysis reveals that Islamic educational philosophy, as represented by Ibn Sina, is not merely an adaptation of Greek philosophy but a transformation of it—aligning reason with revelation to achieve holistic human development. This study also offers critical reflections on the relevance of both traditions in contemporary education, emphasizing the need for an integrative paradigm that unites intellectual, ethical, and spiritual dimensions. The findings contribute to a deeper understanding of how classical philosophical frameworks can inform modern educational thought, especially in bridging the gap between secular rationalism and spiritual humanism.